Stylistic study of the structure and function of passive verb on sixth centurey prose - اشرف شیبانی اقدم; راحله غلامی (تاریخ ادبیات)
Assessment of the stylistic and grammatical relationships in the study of components of a context on the relationship between languages, slogans and their effect on creating meanings can help in explaining linguistic and non-linguistic mechanisms. In certain periods of time, choices affected by different levels of linguistic, literary,… is one of the fundamental factors in the formation of structural distinctions and semantic patterns of a context. In addition to the structural diversity, passive verb indicates other aspects of meaning and also various functions in the six-century prose style and structure of related texts that is very significant in the context of various genres. In this study we have examined the structure and function of the passive verbs in six literal text of the sixth century AH. The data Acquisition of passive verbs of these texts were separately done and then were analyzed and investigated in the statements in terms of semantic. Since the studied texts are of different type of genres as historical, educational-mystic-,…, differences in genres and different semantic context has sometimes revealed contradictory functions and various aspects of the passive verb. According to the studied texts, some of the functions of the passive verb is statement of the general verdict, conveying the meaning of power and social status, conveying the implied message and meaning.